2011
DOI: 10.1007/s12298-011-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic rice genotypes displayed greater adaptation to water-limited cultivation and tolerance to polyethyleneglycol-6000 induced stress

Abstract: Water scarcity and drought have seriously threatened traditional rice cultivation practices in several parts of the world including India. In the present investigation, experiments were conducted to see if the water-efficient aerobic rice genotypes developed at UAS, Bangalore (MAS25, MAS26 and MAS109) and IRRI, Philippines (MASARB25 and MASARB868), are endowed with drought tolerance or not. A set of these aerobic and five lowland high-yielding (HKR47 and PAU201, Taraori Basmati, Pusa1121 and Pusa1460) indica r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The two-weekold rice seedlings were grown hydroponically (Wang et al 2013), and the source of nutrient was from Hoagland solution (Hoagland and Arnon 1950). The solution was replaced once a week and the water level was adjusted on the alternate days (Sandhu et al 2012). Besides, pH of solution was also monitored every two days.…”
Section: Methodsmentioning
confidence: 99%
“…The two-weekold rice seedlings were grown hydroponically (Wang et al 2013), and the source of nutrient was from Hoagland solution (Hoagland and Arnon 1950). The solution was replaced once a week and the water level was adjusted on the alternate days (Sandhu et al 2012). Besides, pH of solution was also monitored every two days.…”
Section: Methodsmentioning
confidence: 99%
“…Secondary traits are important indicators of different physiological, molecular, and developmental changes involved in drought resistance, tolerance, and adaptation mechanisms. The effectiveness of selection for secondary traits such as root thickness, penetration ability and depth, greater hydraulic conductance, xylem thickness and osmotic adjustment, leaf area [85,86], leaf water potential [87], fresh and dry root weight, root volume, relative water content [26], root length [25], photosynthesis [88], early flowering, and harvest index [89] in rice to improve yield under drought is yet to be successfully demonstrated. This also goes for the anthesis-silking interval in maize [90], greenness in sorghum [91], and water-use efficiency in wheat [92].…”
Section: Secondary Traitsmentioning
confidence: 99%
“…The lowest node length was found for Birpala and the highest for Lalkhama (Table 4). Sandhu et al [18] also reported that lowland indica were more sensitive to PEG stress by reducing seedling and root length. Table 4: Mean performance of different genotypes/varieties for different plant characters.…”
Section: Response Among the Genotypes/varietiesmentioning
confidence: 95%